Clinical outcomes in cardiac patients with COVID-19 in an Intensive Care Unit: An integrative review (Research, Society and Development, 2023)
Objective: to identify in the scientific literature the main changes that occur as clinical predictors of unfavorable evolution in patients with heart diseases infected by COVID-19 Methodology: This is an integrative review built based on six steps predefined in the literature. The search for articles took place in the databases: BVS, PUBMED and CINAHAL. Inclusion criteria were: articles published in English, Portuguese or Spanish, from 2020 to 2023, available in full. Exclusion criteria were: duplicate articles, gray literature. Results: Nine scientific articles were selected to compose this review. The present study analyzed a total sample of 24,878 individuals, compiled from nine different articles. Results revealed that patients with COVID-19 who required ICU admission faced an increased risk of cardiac events in the post-infection period. The presence of Troponin I and T was identified as a significant predictor of adverse outcomes in these patients. The presence of pre-existing cardiovascular diseases is a significant risk factor for mortality in patients hospitalized in the ICU due to COVID-19. Patients with diabetes, hypertension and dyslipidemia had a higher risk of death. The most relevant finding was that high levels of troponin increased the chances of complications during hospital stay, ICU admission and mortality. Final considerations: Diabetes, hypertension, dyslipidemia, if present, increase the risk of death from COVID-19. In addition, arrhythmias, bradycardia, myocarditis and ischemia were associated with unfavorable disease outcomes.